Crystal lattice engineering of spinel phases in Mn-oxide doped (Co,Cu,Mg,Ni,Zn)O - Jacob E. Norman; Alexander D. Dupuy; Julie M. Schoenung (Materials Research Letters)
(Co,Cu,Mg,Ni,Zn)O has a rocksalt primary phase with reversible secondary phase transformations. Doping with 2 mol% Mn-oxide created a material with non-reversible phase transformations with multiple secondary phases observed by X-ray diffraction, scanning electron microscopy/energy dispersive spectroscopy, transmission electron microscopy/electron diffraction: Cu-rich tenorite, cubic MnxCo3-xO4 spinel (a = b = c = 8.296 Å, x = 1.06), and distorted tetragonal MnxM3-xO4 spinel (a = b = 5.643 Å and c = 8.795 Å, x = 1.74). The concentration of Mn, x, affects the crystal lattice geometry because of the Mn3+ in the octahedral sites, creating the lattice distortion necessary for a cubic-to-tetragonal transformation. The spinel secondary phases are non-equilibrium and created by controlled dopant chemistry to engineer changes in crystal lattice geometry.